LET’S SPEAK UP : PELATIHAN PUBLIC SPEAKING “PEMUDA PEMBENTUK PERADABAN DI ERA MILLENIAL” - Diah Ayu Septi Fauji; Ismayantika Dyah Puspasari (Jurnal Abdi Masyarakat, 2019)
The development of Indonesia in the future depends on the role of the youth. But now many young people are still embarrassed to speak in public (public speaking), therefore it takes practice on public speaking. The theme of this training is "Youth Forming Civilization in the Millennial Era which aims to train the ability to speak in public by speaking according to the theme. The first training phase: the initial survey of youth constraints in public speaking, the second is material training and the practice of public speaking, the third stage is the accompaniment of the practice of public speaking and evaluation. As a result of this training the participants had the ability to speak in front of an increasing public. Perkembangan Indonesia di mendatang tergantung dari peran pemudanya. Namun saat ini banyak pemuda yang masih malu untuk berbicara di depan umum (public speaking), oleh karenanya dibutuhkan latihan tentang public speaking. Dalam pelatihan ini diambil tema “Pemuda Pembentuk Peradaban di Era Millenial yang bertujuan untuk melatih kemampuan berbicara didepan umum dengan berbicara sesuai tema. Adapun tahap pelatihan ini pertama : survei awal kendala- kendala pemuda dalam berbicara didepan umum, kedua adalah pelatihan materi  dan praktik public speaking, tahap ketiga yaitu pendampingan praktik public speaking dan evaluasi. Hasil dari pelatihan ini peserta memiliki kemampuan berbicara didepan publik yang meningkat.